Fiscal Policy Law Reform Based on Distributive Justice to Reduce Economic Disparity and Improve People's Welfare - Lorraine Rangga Boro; Riswadi Riswadi (Greenation International Journal of Law and Social Sciences, 2025)
Fiscal policy is the main instrument of the state in realizing the goals of the state, including protecting the nation, advancing welfare, and realizing social justice as stipulated in Article 33 paragraph (1) of the 1945 Constitution. One of the important principles in fiscal policy is distributive justice, namely the proportional distribution of burdens and benefits to reduce economic disparities. This study aims to analyze the implementation of distributive justice in Indonesia's fiscal policy and assess the need for legal reform to increase its effectiveness. The method used is normative juridical with an analysis of laws and regulations, including Law Number 17 of 2003 concerning State Finance (Articles 2 and 21), Law Number 7 of 2021 concerning Harmonization of Tax Regulations (Articles 4 and 13), and Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments (Articles 5 and 12), as well as the latest State Budget. The results of the study indicate that although the fiscal legal framework has supported equity, its implementation still faces inequality in budget distribution, low tax compliance, and less than optimal fiscal transfer effectiveness. This study recommends reforming fiscal law based on social justice, strengthening progressive taxation, increasing transparency in state financial management, and optimizing fiscal transfers to achieve equitable public welfare.